The Web, the Users, and the MOS: Influence of HTTP/2 on User Experience - Enrico Bocchi; Luca De Cicco; Marco Mellia; Dario Rossi (Passive and Active Measurement, 2017)
This work focuses on the evaluation of Web quality of experience as perceived by actual users and in particular on the impact of HTTP/1 vs HTTP/2. We adopt an experimental methodology that uses real web pages served through a realistic testbed where we control network, protocol, and application configuration. Users are asked to browse such pages and provide their subjective feedback, which we leverage to obtain the Mean Opinion Score (MOS), while the testbed records objective metrics.